Rhodium(III)-Catalyzed Oxidative Olefination of N-(Naphthalen-1-yl)amides - Wang, Xiaowei; Li, Xuting; Xiao, Jian; Jiang, Yi; Li, Xingwei (Synlett, 2012)
Rhodium(III)-catalyzed oxidative coupling of N-(naphthalen-1-yl)amides with acrylates and styrene was achieved through selective C–H bond activation at the peri position. This reaction proceeded smoothly to give the direct olefination product or the corresponding olefination–cyclization product. High functional-group tolerance was observed
Keywords: oxidative olefination; C–H activation; rhodium